2016
DOI: 10.1002/1873-3468.12387
|View full text |Cite
|
Sign up to set email alerts
|

Atomic‐resolution structure of the phycocyanobilin:ferredoxin oxidoreductase I86D mutant in complex with fully protonated biliverdin

Abstract: Phycocyanobilin:ferredoxin oxidoreductase (PcyA) catalyzes the reduction of biliverdin (BV) to produce phycocyanobilin, a linear tetrapyrrole pigment used for light harvesting and light sensing. Spectroscopic and HPLC analyses inidicate that BV bound to the I86D mutant of PcyA is fully protonated (BVH ) and can accept an electron, but I86D is unable to donate protons for the reduction; therefore, compared to the wild-type PcyA, the I86D mutant stabilizes BVH . To elucidate the structural basis of the I86D muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 23 publications
1
26
0
Order By: Relevance
“…This is consistent with the red shift of the absorbance maximum during DHBV binding at neutral pH. In other FDBRs, such a bathochromic shift is attributed to a protonated, positively charged substrate molecule, requiring an adjacent proton donor (16, 22). Titrating the m Gt PEBB–DHBV complex from pH 7.5 to pH 8.5 resulted in a reversible hypsochromic shift consistent with a deprotonation of Asp-99 (data not shown).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…This is consistent with the red shift of the absorbance maximum during DHBV binding at neutral pH. In other FDBRs, such a bathochromic shift is attributed to a protonated, positively charged substrate molecule, requiring an adjacent proton donor (16, 22). Titrating the m Gt PEBB–DHBV complex from pH 7.5 to pH 8.5 resulted in a reversible hypsochromic shift consistent with a deprotonation of Asp-99 (data not shown).…”
Section: Resultssupporting
confidence: 84%
“…Therefore, we propose the highlighted conformer of Asp-99 as the catalytically active ground state, most likely in a protonated form in the productive enzyme–substrate complex. At the same time, the flexibility of Asp-99 could also be a mechanistic requirement for catalysis as described for PcyA, even though both enzymes differ in their respective catalytic mechanism (22). Notably, a neutron scattering study of PcyA showed protonation of the corresponding conformer in close contact to the D-ring carbonyl in the substrate-bound ground state of the enzyme.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of the latter proceeding via the intermediate 15,16-DHBV with only PcyA specifically reducing the 18-vinyl group of BV first. PcyA is also the best studied member of the FDBR family with a wealth of biochemical, biophysical und structural studies available including a recently published neutron scattering structure [9,12,16,[25][26][27][29][30][31]. Therefore, the discovery of a PcyA-like enzyme (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we speculate that the mutation of Met to Ile led to a disturbance in the hydrogen bonding network of the residues or water molecules involved in the protonation of the BV radical. Interestingly, a mutation of the corresponding Ile86 to Asp86 in PcyA leads also to a complete loss of enzyme activity . It has been speculated that the mutation results in a loss of the flexibility of the central Asp105, a property thought to be crucial for the catalytic activity of PcyA .…”
Section: Discussionmentioning
confidence: 99%
“…PcyA places the conserved Asp105 in close proximity to all four NH moieties of BV in an all-Z,syn configuration (55,59). In PaBphP, the carboxylate side chain of Asp194 from the PxSDIP motif directly interacts with the D-ring of BV in the 5-Z,syn 10-Z,syn 15-E,anti conformation.…”
Section: Far-red-absorbing Mechanisms In Fr-cbcrsmentioning
confidence: 99%